The Elliptic Type Node Configuration and Interpolation in $R^2$ (Journal of Computational Mathematics, 1998)
In this paper, we have obtained an expression of the bivariate Vandermonde determinant for the Elliptic Type Node Configuration in $R^2$, and discussed the possibility of the corresponding multivariate Lagrange, Hermite and Birkhoff interpolation.
Keywords: Multivariate interpolation; Polynomial interpolation; Birkhoff interpolation; Node configuration.